2019
DOI: 10.3390/ijms20246123
|View full text |Cite
|
Sign up to set email alerts
|

Natural Flavonol, Myricetin, Enhances the Function and Survival of Cryopreserved Hepatocytes In Vitro and In Vivo

Abstract: To improve the therapeutic potential of hepatocyte transplantation, the effects of the mitogen-activated protein kinase kinase 4 (MKK4) inhibitor, myricetin (3,3′,4′,5,5′,7-hexahydroxylflavone) were examined using porcine and human hepatocytes in vitro and in vivo. Hepatocytes were cultured, showing the typical morphology of hepatic parenchymal cell under 1–10 µmol/L of myricetin, keeping hepatocyte specific gene expression, and ammonia removal activity. After injecting the hepatocytes into neonatal Severe com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The CFU-s assay can quantify HSCs in bone marrow, and this idea has contributed to fundamental studies in bone marrow transplantation 7,8 . Likewise, as for hepatocyte transplantation, we have confirmed that human hepatocytes survived in the liver of immunocompromised mice 33 . The use of genetically engineered cDNA-uPA/SCID mice, in which liver parenchymal cells are progressively impaired, resulted in more pronounced engraftment of transplanted hepatocytes 7,8 .…”
Section: Discussionsupporting
confidence: 62%
“…The CFU-s assay can quantify HSCs in bone marrow, and this idea has contributed to fundamental studies in bone marrow transplantation 7,8 . Likewise, as for hepatocyte transplantation, we have confirmed that human hepatocytes survived in the liver of immunocompromised mice 33 . The use of genetically engineered cDNA-uPA/SCID mice, in which liver parenchymal cells are progressively impaired, resulted in more pronounced engraftment of transplanted hepatocytes 7,8 .…”
Section: Discussionsupporting
confidence: 62%
“…Bulk-droplet-vitrified hepatocytes had significantly higher viability, better morphology, and higher metabolic activity than non-droplet frozen hepatocytes 93 . Aside from changing the cryopreservation techniques, addition of cell-survival signal, such as myricetin (inhibitor of mitogen-activated protein kinase kinase 4 (MKK4) in culture after thawing cryopreserved hepatocytes aids both the cell survival in vitro and after transplantation in immunodeficient mice 94 .…”
Section: Introductionmentioning
confidence: 99%
“…However, although liver transplantation is an effective treatment, patients have to take immunosuppressive drugs on a lifelong basis, and risk of rejection and need for dietary restrictions exist long after transplantation. While cell transplantation and gene therapy are being examined as novel treatments [ 5 , 8 , 9 , 10 ], their safety and therapeutic efficacies have not yet been determined. From this point of view, human disease models in which clinical equivalent treatments are executable are preferable for the development of novel medical technologies.…”
Section: Discussionmentioning
confidence: 99%
“…The well-known OTCD model animals, sparse-fur (spf/1) mice (ID156, Balb/c background spontaneous mutation mice) show 1/6 the level of OTC activity (wild-type mice: 317.8 ± 51.5 nmol/min/mg, OTCD mice: 53.7 ± 33.5 nmol/min/mg, [mean ± SD, n = 3], unpublished data) and survive for approximately two months (median, 47 days; range: 20–52) [ 5 , 10 ]. In our previous study, hepatocyte transplantation two days after birth significantly prolonged the survival time in OTCD mice [ 10 ]. A mild OTCD model will be more sensitive to detecting the effectiveness of treatments in pigs.…”
Section: Discussionmentioning
confidence: 99%